Consistency of video and photo surveys in measuring attractiveness of forest stands managed with varying intensities - Silvennoinen, Harri; Pikkarainen, Laura; Nakola, Heini; Koivula, Matti; Tyrväinen, Liisa; Tikkanen, Jukka; Chambers, Philip; Peltola, Heli (Finnish Society of Forest Science, 2024)
We evaluated the consistency of video, ordinary photo, and panoramic photo surveys in measuring the attractiveness (recreational use, scenic values etc.) of forest stands managed with varying intensities. We also evaluated possible effects on the results caused by the personal background of citizen respondents and how the respondents experienced the evaluation events. Our experimental sites were in mature Scots pine (Pinus sylvestris L.) forests in eastern Finland and included two replicate sites which were unharvested (control, basal area 26 m2 ha–1), a selective cutting site (basal area 18 m2 ha–1), small openings sites (gap cut) with 5 and 20% retained trees, respectively, and one site which was clear cut with 3% retained trees. In our study, 71 volunteer forestry students evaluated the attractiveness of these sites from an ordinary photo, a panoramic photo, and a video, with a 0–10 scale. Based on this study, the unharvested forest was the most attractive and clear cutting was the least attractive, regardless of the evaluation method. This result was in line with a previous study using on-site evaluations of the same sites. The differences of respondents considering in how easy they felt to assess the attractiveness of the environment as a whole and in using different visualisation methods affected the result, unlike background variables of the respondents. The results of forest attractiveness were consistent between panoramic and ordinary photos, and the attractiveness scoring was slightly higher for them than for the video. We conclude that all the compared visualisation methods seem to be suitable for assessment of the attractiveness of forest views.
Keywords: forest perception; forest preferences; outdoor recreation; landscape management; forest visualisation